Fishing Tourism Business Planning Strategy To Increase People's Income in Lancang Island, Kepulauan Seribu - Mega Fitriani Adiwarna Prawira; Beta Budisetyorini (Politeknik Negeri Bandung, 2021)
Lancang Island is one of the islands in the Kepulauan Seribu Regency with the potential for tourism and fishing activities. Some residents of Lancang Island took advantage of the opportunity by establishing a fishing charter business. This study aims to provide a proper planning strategy for the tourist business unit to increase public income on Lancang Island. The fishing tourism business in Lancang Island includes four units such as Fishing Charter, Boat Rentals, Catering, and Accommodation. The data used are primary and secondary, and the research method is qualitative and presented descriptively. According to research using the BCG Matrix, the entire fishing charter units on Lancang Island are in the Cash Cow quadrant, so concentric diversification is a viable planning strategy. The planning strategies consist of product planning, market and marketing planning, and technology planning tailored to each business unit.